Implementation of Green Infrastructure in Sustainable Transportation in Supporting Urban Mobility: A Literature Review - Aditya Restu Hapriyanto; Hafidzul Azmi (Engineering Proceedings, 2025)
This research explores the implementation of green infrastructure in supporting sustainable transportation systems to improve urban mobility in big cities. The background of this research is based on the need to reduce the environmental impact of the transportation sector, which contributes significantly to carbon emissions and air pollution, especially in dense urban areas. Green infrastructure, such as bicycle lanes, pedestrian-friendly sidewalks, and green open spaces, has been proven to have a positive impact in reducing pollution and improving people’s quality of life. This research aims to analyze how the implementation of green infrastructure can support sustainable transportation and improve the quality of mobility in urban areas, with a focus on case studies of cities such as Copenhagen, Amsterdam, and Singapore, and large cities in Indonesia, including Bandung. Using the literature review method, this research analyzes various reports, journal articles, and statistical data from previous studies regarding the impact of green infrastructure in reducing emissions and promoting environmentally friendly transportation. The results of the discussion show that the implementation of green infrastructure provides various benefits, such as reducing carbon emissions, improving public health, and creating a more comfortable urban environment. Large cities in Europe and Asia have been pioneers in implementing this system, while in Indonesia, cities such as Jakarta, Surabaya, and Bandung have begun to adopt similar concepts with some success, although they still face various challenges. In conclusion, green infrastructure is an important element in sustainable city development that not only improves mobility but also the overall quality of life of society.